Near-road vehicle emissions air quality monitoring for exposure modeling. (1st March 2020) - Moutinho, Jennifer L.; Liang, Donghai; Golan, Rachel; Sarnat, Stefanie E.; Weber, Rodney; Sarnat, Jeremy A.; Russell, Armistead G.
Abstract: Exposure to vehicular emissions has been linked to numerous adverse health effects. In response to the arising concerns, near-road monitoring is conducted to better characterize the impact of mobile source emissions on air quality and exposure in the near-road environment. An intensive measurement campaign measured traffic-related air pollutants (TRAPs) and related data (e.g., meteorology, traffic, regional air pollutant levels) in Atlanta, along one of the busiest highway corridors in the US. Given the complexity of the near-road environment, the study aimed to compare two near-road monitors, located in close proximity to each other, to assess how observed similarities and differences between measurements at these two sites inform the siting of other near-road monitoring stations. TRAP measurements, including carbon monoxide (CO) and nitrogen dioxide (NO2 ), are analyzed at two roadside monitors in Atlanta, GA located within 325 m of each other. Both meteorological and traffic conditions were monitored to assess the temporal impact of these factors on traffic-related pollutant concentrations. The meteorological factors drove the diurnal variability of primary pollutant concentration more than traffic count. In spite of their proximity, while the CO and NO2 concentrations were correlated with similar diurnal variations, pollutant concentrations at the two closely sited monitors differed, likely due to the differences in the siting characteristics reducing the dispersion of the primary emissions out of the near-road environment. Overall, the near-road TRAP concentrations at all sites were not as elevated as seen in prior studies, supporting that decreased vehicle emissions have led to significant reductions in TRAP levels, even along major interstates. Further, the differences in the observed levels show that use of single near-road observations will not capture pollutant levels representative of the local near-road environment and that additional approaches (e.g., air quality models) are needed to characterize exposures. Highlights: Lesser impact from highway source on pollutant levels compared to prior studies. Low predictive power of traffic count on near-road pollutant levels. Results indicative of the effectiveness of mobile source emission controls. Use of observations from a single near-road site can lead to biases in assessing exposures to mobile emissions.